Topotactic Phase Transition Driving Memristive Behavior. Issue 40 (22nd August 2019) - Nallagatla, Venkata R.; Heisig, Thomas; Baeumer, Christoph; Feyer, Vitaliy; Jugovac, Matteo; Zamborlini, Giovanni; Schneider, Claus M.; Waser, Rainer; Kim, Miyoung; Jung, Chang Uk; Dittmann, Regina
Abstract: Redox‐based memristive devices are one of the most attractive candidates for future nonvolatile memory applications and neuromorphic circuits, and their performance is determined by redox processes and the corresponding oxygen‐ion dynamics. In this regard, brownmillerite SrFeO2.5 has been recently introduced as a novel material platform due to its exceptional oxygen‐ion transport properties for resistive‐switching memory devices. However, the underlying redox processes that give rise to resistive switching remain poorly understood. By using X‐ray absorption spectromicroscopy, it is demonstrated that the reversible redox‐based topotactic phase transition between the insulating brownmillerite phase, SrFeO2.5, and the conductive perovskite phase, SrFeO3, gives rise to the resistive‐switching properties of SrFeO x memristive devices. Furthermore, it is found that the electric‐field‐induced phase transition spreads over a large area in (001) oriented SrFeO2.5 devices, where oxygen vacancy channels are ordered along the in‐plane direction of the device. In contrast, (111)‐grown SrFeO2.5 devices with out‐of‐plane oriented oxygen vacancy channels, reaching from the bottom to the top electrode, show a localized phase transition. These findings provide detailed insight into the resistive‐switching mechanism in SrFeO x ‐based memristive devices within the framework of metal–insulator topotactic phase transitions. Abstract : X‐ray photoemission electron microscopy reveals the resistive‐switching mechanism in brownmillerite SrFeO2.5 memristive devices. The resistance change is caused by a reversible phase transition between an insulating brownmillerite SrFeO2.5 and a conductive perovskite SrFeO3− δ phase. Devices with out‐of‐plane oriented oxygen vacancy channels promote localized phase transitions, while devices with in‐plane vacancy channels show nonlocalized phase transitions.